Análise paleoambiental e diagenética dos arenitos carboníferos da Formação Poti da Bacia do Parnaíba, região de Nazaré do Piauí - PI - ARAÚJO, Bruno Eduardo Oliveira de (2018)
The Poti Formation is represented by the siliciclastic deposits of the upper part of the Mesodevonian-Eocarboniferous Sequence of the Parnaíba Basin. It is composed by tine to medium-grained sandstones, with sigmoidal cross-stratification, plane-parallel stratification, supercritically climbing ripple cross-lamination, convoluted laminations and overload structures, interbedded with associated reddish siltstones as part of a delta system. The facies analyses and sandstones petrography of outcrops in the Nazaré do Piauí region (Piauí) allowed for the paleoenvironmental reconstruction and elaboration of the diagenetic sequence events that affected these rocks. Seven facies were identified, grouped into two facies associations, AF1 and AF2. The Delta front association - AF1 presents a succession of 30 meters with coarsening upward pattern arranged in bodies with medium –scale cross stratifications, laterally extensive and formed by unidirectional flow. AF1 is composed of six facies: sandstone with sigmoidal cross stratification (Ss), sandstone with complex crossstratification (Sec), sandstone/silt with supercritical cross-laminated sandstone (ASc), sandstone (Am), sandstone/silt and massivepelile (Pm). The prodelta facies association - AF2 represents a depositional environment of lower energy in comparison to AF1, with the considerable increase of deposition by fall-out. AF2 has five facies: sandstone with sigmoidal cross stratification (Ss), pelite with even-parallel lamination (Pp), sandstone with complex stratification (Aec), sandstone with planeparallel lamination (ASp), sandstone with cross-lamination supercritical (ASc). The paleocurrent measurements obtained in the facies indicate migration of these forms to NW of the Parnaíba Basin. The sandstones are fine to mediumgrainedgranulometry, moderately-sorted and presentesubangulose grains, consisting of monocrystalline and polycrystalline quartz, feldspars (plagioclase and microcline) and chert fragments. In addition to clayey matrix, sometimes encased in quartz grains (coatings), heavy minerals (zircon, tourmaline) and opaque minerals. The main cement types are Fe oxide / hydroxide and carbonaceous (calcitic), defined with alizarin red dyeing. The contacts between the grains are essentially straight, punctual, concave-convex and triple. The pores are intergranular and less commonlyintragranular, móldico, elongated and gigantic. The diagenesis of these sandstones was initiated in the eodiagenesis marked by the mechanical compaction expressed in contorted / crushed mica by quartz grains, forming pseudomatrix, clay infiltration (coatings), alteration of feldspars to clayey minerals. In the mesodiagenesis, they begin with chemical compaction marked by the concaveconvex contacts, formation of carbonaceous cement and generation of secondary porosity well marked by the cellular, gigantic and intragranular pores. In the telodiagenesis, there was precipitation of oxide / iron hydroxide cements, sometimes completely filling the pores (pore filling) and consequent reduction of the secondary porosity.